Radioactive surveillance in peruvian foods - Osores, José (2007)
The concentrations of radionuclides in some Peruvian foodstuffs have been measured. The results of this study can be considered as a first step towards calculating the baseline levels of radioactivity in foodstuffs from Peru. The overall intake of Cs-137 is quite low and no significant radionuclide contamination was found. Therefore the results shows that, between 1990 and 2006, consumers' exposure to artificially produced radioactivity via the food chain, is below the peruvian annual dose limit to members of the public of 1 mSv (millisievert) for all artificial sources of radiation.